1984
DOI: 10.2527/jas1984.592400x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fiber and Virginiamycin on Nutrient Absorption, Nutrient Retention and Rate of Passage in Growing Swine

Abstract: Three balance trials, each involving 12 crossbred gilts averaging 35.2 kg body weight, were conducted to determine the effects of dietary fiber and virginiamycin on nutrient digestibility, mineral absorption and retention, and digesta rate of passage (RP). Two levels of fiber (13.5 and 20.2% neutral detergent fiber) and two levels of virginiamycin (0 and 11 ppm) were used in a 2 X 2 factorial arrangement of treatments. All diets were isonitrogenous and isocaloric. The RP was determined by observing the time re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
1
3

Year Published

1986
1986
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 24 publications
5
34
1
3
Order By: Relevance
“…The effect of virginiamycin on DM digestibility has rarely been investigated (Salinas-Chavira et al, 2009). These authors observed an improvement in DM digestibility in swine, which was attributed to an increase in intestinal feed retention and a reduction in harmful bacteria (Ravindran et al, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of virginiamycin on DM digestibility has rarely been investigated (Salinas-Chavira et al, 2009). These authors observed an improvement in DM digestibility in swine, which was attributed to an increase in intestinal feed retention and a reduction in harmful bacteria (Ravindran et al, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…In swine, virginiamycin enhanced digestion of dry matter, nitrogen (N) and energy (Ravindran et al 1984), metabolizable energy (Vervaeke et al 1979) and minerals (Ravindran et al 1984;Agudelo et al 2007). These benefits were attributable to prolonged intestinal retention time (28%-33%, Ravindran et al 1984) and to reduced intestinal bacterial evolution and corresponding organic acid production (Vervaeke et al 1979). Monensin is a widely used ionophore that is supplemented into feedlot diets to enhance growth performance (Goodrich et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that antibiotics are able to increase apparent N absorption in the small intestine to increase the apparent digestibility of energy and fiber (Ravindran et al 1984 ( 107o) and WB (207a) used were calculated to increase the neutral detergent fiber (NDF) level of the diets 6Vo above that level present in the C diets.…”
mentioning
confidence: 99%